PERAN GURU DALAM PEMBENTUKAN KARAKTER DAN PENCEGAHAN BULLYING DI SEKOLAH DASAR: PENDEKATAN KUALITATIF DESKRIPTIF MELALUI WAWANCARA DAN EDUKASI - Restiana; Neng Sri Mirnawati; Siska Febrianti; Arti Agustin; Paridah; Rijal; Dede Irwan Darmawan; Asep Sahrul Gunawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
2. Classroom Action Research (CAR) focuses on solving classroom problems directly, while traditional research focuses on developing general educational theories. CAR is practical, flexible, and conducted by teachers through planning, action, observation, and reflection. Traditional research is more formal and uses larger samples. CAR is suitable for classroom problems because teachers can immediately apply and improve teaching strategies. 3. Reflection after Cycle I is done by evaluating the results of the action, including student participation and learning outcomes. The teacher identifies weaknesses and improves the strategy for Cycle II. For example, if students are still shy to speak English, the teacher can add vocabulary practice or group activities in Cycle II. 4. Observation helps teachers collect information about student learning. Reflection helps evaluate teaching effectiveness, while collaboration allows teachers to share ideas and feedback. These elements help improve teaching quality and student achievement. 5. One classroom problem that can be researched through CAR is students’ low confidence in speaking English. The teacher can use role play or group discussions to increase participation. CAR helps improve student learning outcomes and also develops the teacher’s professional skills.